1997
DOI: 10.1021/np9605495
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry-Dependent Cytotoxicity of Some Artemisinin Derivatives

Abstract: We determined the cytotoxicity of some artemisinin derivatives against EN2 tumor cells using the MTT assay. Artemisinin (1) was clearly more cytotoxic than deoxyartemisinin (2), which lacks the endoperoxide bridge. Ether-linked dimers of dihydroartemisinin with defined stereochemistry were found to differ in the extent of cytotoxic effect on EN2 cells. The nonsymmetrical dimer (3) was more cytotoxic than the symmetrical dimer (4). The nonsymmetrical dimer of dihydrodeoxyartemisinin (5) lacking the endoperoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 18 publications
1
90
0
1
Order By: Relevance
“…Cytotoxicity testing in vitro was done by the method of modified Woerdenbag et al (15,16). The MTT metabolic assay was carried out in seeded at the density of 1x10 4 cells/ well in 96-well flat-bottom cell culture plates with 100 μL of opti-MEM and 24-48 hours incubation at 37ºC, 5% CO 2 ..…”
Section: Mtt Testmentioning
confidence: 99%
“…Cytotoxicity testing in vitro was done by the method of modified Woerdenbag et al (15,16). The MTT metabolic assay was carried out in seeded at the density of 1x10 4 cells/ well in 96-well flat-bottom cell culture plates with 100 μL of opti-MEM and 24-48 hours incubation at 37ºC, 5% CO 2 ..…”
Section: Mtt Testmentioning
confidence: 99%
“…Cell viability and cytotoxic activity profile of the compounds were analyzed using the MTT assay (29,30,31). MTT is cleaved to formazan by the "succinate-tetrazolium reductase" system (EC 1.3.99.1) which belongs to the mitochondrial respiratory chain and is active only in viable cells.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Cytotoxicity testing in vitro was done by the method of modified Woerdenbag et al (30,31). The MTT metabolic assay was carried out in seeded at the density of 1x10 4 cells/well in 96-well flat-bottom cell culture plates well plates with 200 μL of opti-MEM (invitrogen, USA) and incubated for 24 hours at 37ºC, 5% CO 2.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…[11][12][13][14][15] In addition to their wellknown antimalarial activity, artemisinin and its derivatives also possess potent antiangiogenic activity, [16][17][18][19][20][21][22][23] and several research groups have demonstrated potential antitumor properties for this compound class. 20,[24][25][26][27][28][29][30][31] We have shown that non-acetal 12β(C-C)-type amide derivatives of deoxoartemisinin exhibit higher in vitro anticancer activity 22) along with 20 times greater acid stability than acetal (C-O)-type derivatives of artemisinin. 32) One approach that has been developed to improve anticancer activity is the use of hybrid drugs, which incorporate two drugs into a single molecule 33) and can impact multiple targets simultaneously.…”
mentioning
confidence: 99%